Hypothyroidism and hyperprolactinemia showed positive correlation in women with primary and secondary infertility - Valvekar, Umakant; Lakshmi, Santhana; Kumar, Amar Nagesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hyperprolactinemia is a common problem which is encountered in reproductive disorder. Hyperprolactinemia is usually associated with menstrual and ovulatory disorders like amenorrhea, oligomenorrhea, anovulation, ovulatory cycle with short or inadequate luteal phase and galactorrhea. Hypothyroidism may also cause failure to ovulation in women of reproductive age group. This study has been conducted to correlate prolactin and thyroid stimulating hormone (TSH) levels in primary and secondary infertility. Methods: The study comprises of 120 female subjects, which were divided into three groups-healthy control women (group 1), women with primary infertility (group 2) and secondary infertility (group 3). Fasting blood samples were collected between 7 AM to 8 AM. Hormones T3, T4, TSH and prolactin levels were estimated by enzyme linked fluorescent immunoassay (ELFA) method in all the study subjects. Results: In the present study there was a positive correlation of hyperprolctinemia with hypothyroidism in both primary and secondary infertile women. Conclusions: Hence it is recommended to screen serum prolactin levels along with thyroid hormones screening in women with infertility problems.